'Triadic' shared decision making in mental health: Experiences and expectations of service users, caregivers and clinicians in Germany. (15th January 2021) - Schuster, Florian; Holzhüter, Fabian; Heres, Stephan; Hamann, Johannes
Abstract: Background: Shared decision making (SDM) in mental health may contribute to greater patient satisfaction and is sometimes associated with better health outcomes. Here, SDM should not only involve service users and clinicians but also involve the service users' caregivers. Aim: This study aimed to achieve better insight into the current SDM patterns of triads of service users, caregivers and clinicians in inpatient mental health care and the three parties' expectations towards the prospects of triadic SDM. Design: The current research uses data from a representative cross‐sectional study on caregivers in psychiatric inpatient treatment. We analysed data on n = 94 triads of service users, their caregivers and their clinicians. Results: All three parties acknowledge caregivers to be of great support to monitor the progress with mental disease. The caregiver's role during consultations is most often described as being an expert, receiving or providing information and supporting service users. However, caregivers at times try to seek support for themselves during caregiver‐clinician interaction, or their behaviour was described as unhelpful. The potential prospects of caregiver involvement are clearly acknowledged despite the low implementation of caregiver involvement in this sample (only in one‐third of the cases). Conclusion: Triadic SDM rarely takes place in routine inpatient care. First, there should be a focus on interventions aiming at inviting caregivers to consultations. Only in the second step should a better conceptualisation of triadic SDM be undertaken. Public Contribution: Early results were discussed with a local peer support group for caregivers of individuals living with mental illness.